Flexible Citizenship in Wena Poon’s Short Stories: Writing at the Interstices of Asia and America - Chang, Stewart (SARE: Southeast Asian Review of English, 2017)
United States- based Singaporean author Wena Poon writes to the multi-layered complexities of transient transnational identity. Her short stories, produced within the interstices of her professional work as a multi-national corporate attorney, reveal a sensitivity towards the transient and mobile subject that, beyond Neel Chowdhury’s assessment that they "lapse...into the cliches that bedevil stories of Asian deracination," speaks to multi-nationals whose lives are characterised by constant movement and flux between countries. On the surface, Poon bills her work as literature by a transnational author for transnational readers, yet nested within many of her short stories are considerations about the larger consequences of Western globalisation and accelerated capital growth in Asia that have led to "flexible citizenship," particularly for Singaporeans away from their homeland living in the larger Chinese diaspora in America and across the globe.